Forests nature, people and power - Doornbos, Martin (Ed.); Saith, Ashwani (Ed.); White, Ben (Ed.) (Oxford Black well, 2000)
Forest the arenos of struggles and conflicts,in which both trees and forest dwellers,frequently find themselves on the losing side, focusing on the forests of Africa, Asia and Latin America. This volume highlights four dimensions; the array of ongoing con
Keywords: Forests and forestry; Forest conservation; Agriculture